Editorial (@limentech, Ciencia y Tecnología Alimentaria, 2024)
Volume 22, number 1 of 2024 of the @limentech Magazine focuses on the dissemination of knowledge in Food Science and Technology, presenting research by national and international authors. The articles address topics such as the use of natural extracts for pest control, the evaluation of the potato production system in Santander, the sensory quality of food products (such as cheese and goat meat), and the analysis of cadmium in cocoa beans. Aspects of microbiological quality in food are also examined, including the identification of pathogenic microorganisms in poultry feed.In addition, a study on food safety in children with acute malnutrition is included, encouraging the exchange of experiences and the generation of collaborative strategies. The journal seeks to enrich the academic landscape and address the challenges of food insecurity in compliance with the objectives of FAO and WHO. The scientific community is invited to contribute their research through the Open Journal platform or institutional email.For more information, visit the journal's website: Revista @limentech.